Tingkat Stres Narapidana ditinjau dari Masa Tahanan dan Frekuensi Membaca Alquran - Kholifah Umi Sholihah; Dian Ratna Sawitri (Jurnal Psikologi Islam dan Budaya, 2021)
This study aims to examine the relationship between detention duration and stress and to determine the level of stress in terms of the frequency of reading the Alquran by inmates. This research is a quantitative correlational and comparational research. This study was conducted in detention houses X and Y involving 63 male inmates. The sampling technique used is purposive sampling. The data collection technique was carried out using the Stress Scale. The results of this study indicate that there is no relationship between the length of detention and stress, however there is a difference in stress in terms of the frequency of reading the Alquran. The conclusion obtained in this study is that the activity of reading the Alquran is important for inmates.